THE FIGURATIVE LANGUAGES TRANSLATION ANALYSIS IN CONFESSIONS OF A SHOPAHOLIC NOVEL BY SOPHIE KINSELA - N.Rani Kartika, - (2011)
The research of the study entitled "The Figurative Languages Translation Analysis in Confessions of a Shopaholic Novel by Sophie Kinsela". The study presented an analysis of figurative languages that were found in the novel and also the translation procedures that were applied in translating those figures of speech in Sophie Kinsela's novel. In accordance with the problem of the study, a descriptive qualitative method was applied to examine the data collected. There result of the research indicated that there were 176 items of figures of speech found in the selected chapters in the novel. Afterward, numbers of the figures of speech were classified into three groups. In details, the classification of figurative languages and its figures of speech, frequencies and percentages were presented as follows: The type of figurative comparison (43.1%), contains metaphor (21 items or 11.93%), simile (25 items 14.20%), personification (30 items or 17.05%). Next is the type of figurative substitution (33.52%), contains metonymy (41 items or 23.29%), synecdoche (18 items or 10.23%). And the last is the type of figurative exaggeration (23.21%), contains hyperbole (34 items or 19.23%) and litotes (7 items or 3.98%). Several procedures were applied by translator in translating figurative languages. Those procedures were couplet (34 items or 19.32%), transposition (28 items or 15.91%), literal (24 items or 13.64%), transference (21 items or 11.93%), reduction (16 items or 9.09 %), addition (14 items or 7.95%), modulation (12 items or 6.82%), naturalization (8 items or 4.54%), paraphrase & equivalence (5 items or 2.84%), synonymy (3 items or 1.70%), recognized, expansion and triplet (2 items or 1.14%). The figurative languages translation in the novel Confessions of a Shopaholic is categorized as "Good" level (697 points or 66.0%), it is followed by "Fair" level (208 points or 19.69%), "Excellent" level (107 points or 10.13%), and "Bad" level (44 points or 4.17%). The last but not least, the findings of this study was expected to give a wider perspective and knowledge about translation field.